Chemical-free graphene by unzipping carbon nanotubes using cryo-milling. (August 2015) - Tiwary, C.S.; Javvaji, B.; Kumar, C.; Mahapatra, D.R.; Ozden, S.; Ajayan, P.M.; Chattopadhyay, K.
Abstract: Current paper reports synthesis of chemical free graphene by unzipping of the carbon nanotubes (CNTs) using high strain rate deformation at 150 K. A specially designed cryomill operating at 150 K was used for the experiments. The mechanism of unzipping was further explored using molecular dynamics (MD) simulations. Both experimental and simulation results reveal two modes of unzipping through radial and shear loading.